Biological Roles and Clinical Significance of Exosome-Derived Noncoding RNAs in Bladder Cancer - Tong, Yonghua; Liu, Xiao; Xia, Ding; Peng, Ejun; Yang, Xiaoqi; Liu, Hailang; Ye, Tao; Wang, Xinguang; He, Yu; Xu, Hua; Ye, Zhangqun; Chen, Zhiqiang; et al. (Frontiers in Oncology, 2021)
Bladder cancer (BCa) is a common heterogeneous urinary system tumor with high malignancy and limited advancement in treatment. Limited understanding of BCa has not contributed to any significant progress in diagnosis or treatment, exploring the mechanisms underlying BCa has become an urgent research focus. Exosomes, a type of extracellular vesicle (EV), have drawn substantial interest for their important roles in mediating intracellular communication. Exosomes shuttle numerous bioactive molecules, and non-coding RNAs (ncRNAs) are among the most numerous. ncRNAs including microRNA, long-noncoding RNA, and circular RNA are sorted and packaged into exosomes selectively and transferred into recipient cells to regulate their function. Exosomal ncRNAs are associated with hallmarks of BCa, such as proliferation, apoptosis, epithelial-mesenchymal transition (EMT), cell cycle arrest, lymphangiogenesis, and chemotherapy resistance. Exosomal ncRNAs can also be detected in urine and serum, making them encouraging biomarkers for BCa diagnosis and prognosis. More importantly, exosomes exhibit excellent biocompatibility and potential for diversified applications. The delivery of bioactive substances and drugs into specific cells has become a promising approach for precision therapy for BCa patients. In addition, cancer vaccines have also received increasing attention. In this review, we summarize the current research on the regulatory roles of exosomal ncRNAs in BCa tumorigenesis and progression, as well as their potential clinical value in accelerating the diagnosis and therapy of BCa.